Deep fungal infections diagnosed in Johannesburg in the period 1987-1996 - Klevansky, David Wayne (My University, 2014)
The aim of this study was to update the knowledge concerning the types and relative prevalence of the various deep fungal infections of the skin encountered in the Johannesburg region. Two previous studies have been published concerning deep fungal infections in this area, first by Lurie in 1955 (1) and the last by Martin and Berson in 1973 (2). Over a ten year period from 1987 to 1996, 120 cases of deep fungal infection of the skin were recorded.This included patients with sporotrichosis (the commonest disease), mycetoma, nocar dial infections, chromoblastomycosis, actinomycosis and blastomycosis. The present data were compared with the two previous studies and it was found that the relative incidence of sporotrichosis, chromoblastomycosis and actinomycosis has declined,while that of blastomycosis appears to have increased in recent years. The relevant South African literature regarding deep fungal infections is reviewed. In this study, three species are reported to cause deep fungal infections in South Africa for the first time, viz. Nocardia dassonvillei, Actinomyces meyeri andNocardia caviae,.